Cold Acclimation Does Not Alter Physiological or Perceptual Responses During Subsequent Exercise in the Heat - Jones, Douglas M.; Rostomily, Kaitlyn A.; Pautz, Carina M.; Ito, Danica W.; Bailey, Stephen P.; Roelands, Bart; Buono, Michael J.; Meeusen, Romain (Military medicine, 2017)
Warfighters often train and conduct operations in cold environments. Specifically, military trainees and divers that are repeatedly exposed to cold water may experience inadvertent cold acclimatization, which results in body heat retention. These same warfighters can quickly switch between environments (cold to hot or hot to cold) given the nature of their work. This may present a risk of early onset of hyperthermia when cold-acclimatized warfighters are subsequently exposed to physiological insults that increase body temperature, such as exercise and heat stress. However, there is currently no evidence that suggests this is the case. The purpose of this work, therefore, is to determine what impact, if any, repeated immersion in cold water has on subsequent exercise in the heat. Twelve healthy subjects (values in mean ± SD: age, 25.6 ± 5.2 years; height, 174.0 ± 8.9 cm; weight, 75.6 ± 13.1 kg) voluntarily provided written informed consent in accordance with the San Diego State University Institutional Review Board. They first completed 120 minutes of moderate treadmill walking in 40°C and 40% relative humidity. During this trial, subjects' physiological and perceptual responses were recorded. Twenty-four hours later, subjects began a cold acclimation protocol, which consisted of seven, 90-minute immersions in cold water (10°C, water level to chest). Each immersion was also separated by 24 hours. Subjects then repeated a subsequent trial of exercise in the heat 24 hours after the final immersion of the cold acclimation protocol. Results from cold acclimation revealed no change in core temperature, a decrease in skin temperature, and attenuated shivering and lactate responses, which supports a successful insulative-hypothermic cold acclimation response. This type of cold acclimation response primarily results in heat retention with associated energy conservation. Findings for heat trials (pre-cold acclimation and post-cold acclimation) revealed no differences between trials for all measurements, suggesting that cold acclimation did not influence physiological or perceptual responses during exercise in the heat. Our findings indicate that military divers or trainees that are frequently exposed to cold water, and hence have the ability to experience cold acclimatization, will likely not be at greater risk of increased thermal strain when subsequently exposed to physical activity in hot environments. In this study, no physiological or perceptual differences were observed between trials before and after cold acclimation, suggesting that cold acclimation does not present a greater hyperthermia risk during subsequent exercise in the heat.